2023
DOI: 10.3390/su151310371
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Organizational Unlearning in Manufacturing Firms’ Sustainable Digital Innovation: The Mechanism of Strategic Flexibility and Organizational Slack

Abstract: This study explores the underlying mechanisms of achieving sustainable digital innovation in the context of manufacturing companies. Building on the perspective of organizational unlearning, we propose that organizational unlearning could disrupt current innovation routines and positively relate to the sustainability of digital innovation, the features of which are self-referential improvement and iterative scalability. This study conducted a questionnaire survey of 274 Chinese manufacturing companies and used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 107 publications
1
1
0
Order By: Relevance
“…Furthermore, it has been demonstrated that organizational slack plays a mediating role in the relationship between organizational learning and organizational effectiveness. Similarly, as found in the literature, the conducted research suggests that having organizational slack (specifically in the financial construct used in the study) somewhat strengthens the impact of organizational learning on organizational effectiveness (Zhao, Yan, 2023). Additionally, no significant differences were observed between family-owned and non-family-owned firms in the analyzed area.…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, it has been demonstrated that organizational slack plays a mediating role in the relationship between organizational learning and organizational effectiveness. Similarly, as found in the literature, the conducted research suggests that having organizational slack (specifically in the financial construct used in the study) somewhat strengthens the impact of organizational learning on organizational effectiveness (Zhao, Yan, 2023). Additionally, no significant differences were observed between family-owned and non-family-owned firms in the analyzed area.…”
Section: Discussionsupporting
confidence: 71%
“…This paper validates the dual-mediating role of learning and unlearning at the individual level in digital transformation. In addition, a previous study proposes that organizational unlearning could disrupt current innovation routines and positively relate to the sustainability of digital innovation in manufacturing companies [75]. Thus, this study explicitly stresses the dual roles of learning and unlearning in an employee's adaptation process to digital transformation.…”
Section: Discussionmentioning
confidence: 85%